Investigating the Relationship of Spiritual Experiences and Hardiness withOccupational Stressamong Nurses in Zabol - Jenaabadi, Hossein; Nakhaeei, Somaie (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Thepresent study aimedto investigate the relationship of spiritual experiences and hardiness with occupational stress among nurses. This is a descriptive-survey study. The research population consisted of nurses working as formal, contractual, provisional, andprojectemployees at hospitals of Zabol. The sample consisted of 173 nurses. Research instruments includedthe Spiritual ExperienceScale for Studentsdeveloped byGhobari-Bonab,Kobasas Hardiness Questionnaire and the Expanded Nursing Stress Scale (ENSS). The content validity was checked and the reliability of these three questionnaires was estimated using the Cronbach's alpha coefficients. This coefficient for these three questionnaires was 0.75, 0.76, and 0.85 respectively. The Pearson correlation, stepwise regression, independent t-test, and one-way ANOVAwere used to analyze the obtained data. Results revealed that there was a negative significant relationshipamong spiritual experiences, hardiness and occupational stress. Moreover,no significant relationship was found between organizational commitment and occupationalstress. However, it was revealed that there was a negative significant relationship between occupationalstress,control, and challenge. The findings alsoindicated thatamong the predictor variables of nurses stress, in the first step thetranscendent experiences,in the second step prosperity,in the third step belief in God, in the fourth step negative experiences,and in the fifth step finding meaning in lifeenteredthe predictionmodel.